THE ROLE OF PRENATAL CLASSES IN EXCLUSIVE BREASTFEEDING: EVIDENCE FROM PAPUA, INDONESIA - Latifah, Leny; Laksono, Agung Dwi; Soerachman, Rachmalina; Mulyantoro, Donny Kristanto; Khairunnisa, Marizka; Kusumawardani, Hastin Dyah; Hidayat, Taufiq; Samarang; Musoddaq, Muhamad Arif (Universitas Airlangga, 2025)
Background: Exclusive breastfeeding (EBF) is a lifesaving practice for infants in vulnerable conditions. Therefore, it is crucial to ensure the optimization of EBF coverage in disadvantaged areas. One of the barriers to EBF is limited maternal knowledge, and prenatal classes are designed to improve maternal health knowledge and practices. Aims: The study aimed to analyze the role of prenatal classes in supporting EBF in Papua. Methods: The cross-sectional study examined 640 mothers with children aged 0-5 months from the Papua Region. Prenatal classes were an exposure variable, while EBF practice served as an outcome variable. Nine control variables, including age, marital status, education, work, wealth, sex, infant age, and early initiation of breastfeeding (EIBF), were incorporated into the analysis. Binary logistic regression test was used for analysis. Results: The proportion of EBF in Papua is 50.7%. Mothers who participated in prenatal classes were 1.560 times more likely to practice EBF than those who did not (AOR = 1.560; 95% CI [1.476-1.649]). Additionally, the study identified nine control variables related to EBF in the Papua Region: type of residence, maternal age group, maternal marital status, education level, employment status, wealth status, infant age, infant sex, and EIBF. Conclusion: Participation in prenatal classes is positively associated with the achievement of EBF practice in the Papua Region. Additional characteristics associated with a higher likelihood of EBF among Papuan mothers included having a higher level of education and employment, living in rural regions, experiencing poverty, being married, and achieving successful EIBF. Keywords: exclusive breastfeeding, Papua, prenatal classes, public health, public health nutrition